Reproductive behaviour and longevity: Evidence from Chinese centenarians - Shuo Zhang; Si-qing Zhang; Hua-lei Yang; Jia-hao Wang; Yuan-yang Wu (Homo)
With the implementation of the three-child policy in China, the debate between fertility and health and longevity has again become a hot topic in the era of increasing ageing. This study aimed to explore the association between reproductive behaviour and longevity of older women and men in China. Based on data from the Chinese Longitudinal Healthy Longevity Survey (CLHLS) from 2014 to 2018, a total of 1428 deceased older people were enrolled in the study, including 421 centenarians and 1007 non-centenarians. The analysis of the association between fertility and longevity was conducted in the multivariate logistic regression. Compared to women aged 99 years and below, centenarian women had significantly fewer children (p < 0.01), fewer sons (p < 0.01) and fewer daughters. Centenarian men had more children, more daughters and fewer sons. For both men and women, centenarians were significantly characterized by later age at first birth (p < 0.01) and later age at last birth (p < 0.01). Centenarians were significantly characterized by having children and having a daughter, however, non-centenarians were significantly characterized by having a son (p < 0.01). The association between fertility and health of both men and women should be taken into account in the development of fertility policies and supporting policies. Fertility levels should be increased without compromising the health benefits of individuals in their later years.